Pertussis as health care workers infectious disease - The clinical case with a commentary - Ernest Kuchar; Aneta Nitsch-Osuch; Leszek Szenborn (Nofer Institute of Occupational Medicine, 2013)
We discuss the changing epidemiological situation of pertussis observed in recent years, with a focus on the shift of cases from young children to older age groups, teenagers and adults. Whooping cough may affect healthcare workers who belong to a high-risk group and cause hospital infections. We present a case report of pertussis in a nurse and the recommended prophylactic measures in healthcare workers. The current definition and diagnosis of pertussis is also discussed. The clinical course of pertussis can be significantly alleviated and highly non-specific, with no typical coughing and vomiting in people vaccinated against whooping cough a few years earlier. Pertussis should be considered in the differential diagnosis of cough lasting more than fourteen days. Improvement of the epidemiological situation requires, besides immunization of infants, regular and universal booster immunization for adolescents and adults. Vaccinations for health care workers of neonatal and pediatric wards are recommended in the National Program of Immunization for 2013. It seems that booster vaccination of health care workers with a triple vaccine against diphtheria, tetanus and acellular pertussis (dTpa) of the reduced quantity of antigens, particularly of health workers caring for infants, children and the elderly, may be the most effective way to reduce the risk of pertussis transmission in the health care environment. Med Pr 2013;64(5):731-739